Role of Traditional Knowledge in a Knowledge Society: Interpreting Insights for Contemporary Use - Singh, R. P. (INDIAN EDUCATIONAL REVIEW, 2009)
This paper seeks to examine the possibility of the use of traditional knowledge/insights developed over a period of time in the Knowledge Society. The author asks the present generation not to neglect it and not allow it to be lost in the haze of antiquity. It also gives reasons why this knowledge continues to be relevant in our contemporary societies. This is perhaps one reason why the National Knowledge Commission has specifically mentioned the importance of this traditional knowledge in our educational system. “A technologist first builds a transport to travel on earth, second in the water and the third capable to fly in the sky. 0 person! Such technologists impart happiness, triumph and make us powerful. It connects or regulates such movements in the ocean with thoroughness. Likewise, they should train more people to multiply the number of more technologists.” Rigveda,2. 18.2